Management of Financial Tools for the Development of Microenterprises in the North Cone of Metropolitan Lima Year 2017 - Vicente Armas, Edgar (2018)
Lima Metropolitan (2014), has approximately 862 thousand microenterprises, of which 172 thousand are in the districts of the North Cone; of this total, a sample of 562 microenterprises has been taken, of which 283 are dedicated to the trade activity; 194 come running between 1 to 3 years; they work from 1 to 10 people in 523 micro-businesses; in 430 micro-enterprises the person in charge of finances is the owner; 52% have the financial status; 59.5% declare that they use it to declare taxes. They have financial statements, use as a financial tool in management, 99.1% Balance, 98.9% the income statement, 92.1% cash flow, and 96.9% budget. As for whether you use accounting or financial software, 22.8% state that they do use it; 53.6% claim to be subject to credit and 62.2% declare the need for financing as working capital.